Letter: Drug interaction in resmetirom times - Zhou, Xiao‐Dong; Liu, Wen‐Yue; Targher, Giovanni; Byrne, Christopher D.; Zheng, Ming‐Hua (Alimentary pharmacology & therapeutics, 2024)
LINKED CONTENT This article is linked to Harrison et al paper. To view this article, visit https://doi.org/10.1111/apt.17734